Revaloración de la cuenta propiedad planta y equipo del Gobierno Autónomo Descentralizado Parroquial de Ricaurte del periodo 2022. - Cotera Pita, Bryan Damián (2023)
The revaluation of Property, Plant and Equipment is a very important process for organizations because it allows the values of their assets to be kept updated at their market value, thus providing a more accurate representation of their financial situation. The objective of this case study is to analyze the revaluation of the Property, Plant and Equipment account according to IAS 16 in the Ricaurte Parish GAD for the period 2022. The approach of the study is mixed; while the types of research used were documentary and field. The research method used was the inductive one. On the other hand, the techniques used to collect information were an interview with the institution's accountant to know parameters related to the management of financial information of the PPE and application of IAS 16; A documentary observation was also applied, since the information contained in the entity's financial statements was analyzed. The investigation allowed us to conclude that: The real value of the PPE account according to the revaluation analysis carried out is $29,049.42. Therefore, an increase in said heat is evident with respect to that stipulated in the financial statement of the institution. The parish GAD omits the importance of valuing business assets with the intention of having timely and reliable information for the internal decision-making process.